1990
DOI: 10.1002/ana.410280608
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar and frontal hypometabolism in alcoholic cerebellar degeneration studied with positron emission tomography

Abstract: Local cerebral metabolic rate for glucose was studied utilizing 18F-2-fluoro-2-deoxy-D-glucose and positron emission tomography (PET) in 14 chronically alcohol-dependent patients and 8 normal control subjects of similar age and sex. Nine of the 14 patients (Group A) had clinical signs of alcoholic cerebellar degeneration, and the remaining 5 (Group B) did not have signs of alcoholic cerebellar degeneration. PET studies of Group A revealed significantly decreased local cerebral metabolic rates for glucose in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(103 citation statements)
references
References 40 publications
6
95
0
2
Order By: Relevance
“…Tambi茅n con t茅cnicas de neuroimagen funcional se ha observado un mayor efecto del alcohol sobre los l贸bulos frontales. Por ejemplo, se ha encontrado una reducci贸n del metabolismo de la glucosa en estas 谩reas en alcoh贸licos sin otras patolog铆as neurol贸gicas (Adams, Gilman, Koeppe, Kluin, Brunberg, Dede et al, 1993;Gilman, Adams, Koeppe, Berent, Kluin et al, 1990). Por otro lado, Jaatinen, Riikonen, Riihioja y Kajander (2003) demostraron que el consumo cr贸nico intermitente de alcohol, el equivalente al consumo de fin de semana, ocasiona un descenso del metabolismo energ茅tico de las neuronas en la corteza prefrontal que contribuye al proceso de neurodegeneraci贸n y al consiguiente deterioro de las funciones cerebrales.…”
Section: Discussionunclassified
“…Tambi茅n con t茅cnicas de neuroimagen funcional se ha observado un mayor efecto del alcohol sobre los l贸bulos frontales. Por ejemplo, se ha encontrado una reducci贸n del metabolismo de la glucosa en estas 谩reas en alcoh贸licos sin otras patolog铆as neurol贸gicas (Adams, Gilman, Koeppe, Kluin, Brunberg, Dede et al, 1993;Gilman, Adams, Koeppe, Berent, Kluin et al, 1990). Por otro lado, Jaatinen, Riikonen, Riihioja y Kajander (2003) demostraron que el consumo cr贸nico intermitente de alcohol, el equivalente al consumo de fin de semana, ocasiona un descenso del metabolismo energ茅tico de las neuronas en la corteza prefrontal que contribuye al proceso de neurodegeneraci贸n y al consiguiente deterioro de las funciones cerebrales.…”
Section: Discussionunclassified
“…This finding could suggest that metabolic dysfunction occurs before GM shrinkage, in agreement with a study showing hypometabolism in alcoholic patients without brain atrophy. 12 Other studies reported a relationship between global brain metabolism and volume in alcoholic patients, 1,13 suggesting, according to the authors, a causal relationship between cortical atrophy and brain metabolism or vice versa. 13 Such discrepancies may be explained by several methodological issues.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3] Previous studies have shown alcohol-related grey matter (GM) volume deficits predominantly in the frontal cortices. 3,4 The dorsolateral cortex showed GM shrinkage, reaching up to 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) studies consistently reveal frontocortical recruitment by behavior control tasks (Horn et al, 2003;Li et al, 2006a;Li et al, 2006b;Ridderinkhof et al, 2004), such as risk-taking . SUD subjects also show blunted frontocortical glucose utilization (Gilman et al, 1990;Samson et al, 1986) and blood flow (Bolla et al, 2003), that correlate with reaction times (Dao-Castellana et al, 1998) and risky choices (Bolla et al, 2003;Fishbein et al, 2005) in decision-making tasks. These findings suggest a possibility that higher-order cortical regions that maintain or integrate representations of potential penalties for immediately rewarding behavior are impaired in persons with SUD.…”
Section: Introductionmentioning
confidence: 99%